Topology tools for network analysis on gis platforms - Aguero, Carlos Alberto (2019)
Vector Geographic Information Systems (GIS) have network analysis tools thatare of great importance in the modeling of electrical networks and especially for anystudy based on the interconnectivity of their sections. This work presents thedevelopment of computer tools that use as a basis the analysis of network topologiesand their application for the detection of areas interconnected or affected byinterruptions in supply, the identification and selection of each of the elementsrepresented and the possibility of exchanging data with other calculation software.